KH. A. WAHID HASYIM DAN PEMBAHARUAN PENDIDIKAN PESANTREN - Didin Kurniadin (Istitut Ilmu Al-Qur'an (IIQ) An-Nur Yogyakarta Komplek PP An Nur Ngrukem PO BOX 135 Bantul 55702 Yogyakarta Tlp/Fax (0274) 6469012. http://jurnalannur.ac.id/, 2011)
The Renewal of thought of Islamic boarding schools education has been done bymany Indonesia Muslim intellectuals. One of them is Abdul Wahid Hasyim. He isnot only known as a prominent figure of the Indonesia’s independence movement,but also known as a famous ulama and Muslim Intellectual in Indonesia. Hiseducational and religious thoughts much influenced the educational system untilnow; for example about the importance of religious teaching and education in publicschools, both state and private. Another important idea is the establishment of theState Islamic University (PTAIN) which is now to be the IAIN / UIN / STAIN,and the establishment of place or institution for Indonesia Pilgrimage Committee(PHI).